Genetic relationship of Jatropha curcas L.from Samarahan, Lundu and Kalimantan detected by random amplified polymorphic DNA (RAPD) markers - Syarifah Nur Liyana, binti Syd Amra (Universiti Malaysia Sarawak (UNIMAS), 2012)
Jatropha curcas L. from family Euphorbiaceae are also known as "Jarak" is getting attention nowadays even in Malaysia also this plant are being study from every aspects. A total of five samples were collected from Samarahan, Lundu and Kalimantan and planted in UNIMAS green house. Fresh Jatropha's leave sample was taken for the DNA extraction, DNA quantification (gel electrophoresis), and peR amplification ofDNA samples to gain the genetic relationship. From the result, a total of48 alleles were generated from 9 OPF primers with 54.2% were polymorphic. OPF-08 primer produced highest polymorphic bands while OPF-17 and OPF-I8 shows all monomorphic bands. Two cluster was constructed which unknown UNIMAS samples was in cluster I while the rest samples were in cluster II, the genetic relationship was analyzed through dendogram using NTSYS-pc 2. I software. An UPGMA dendogram based on the polymorphic bands showed highest genetic similarity between Kg. Rembus I and Kg. Rembus 2 while the lowest similarity is between unknown UNIMAS sample with Kg. Rembus 2. In conclusion, Jatropha curcas L. in Samarahan, Lundu and Kalimantan have quiet high genetic variation among accessions tudied. This study may provide genetic information for next study on Jatropha curcas L. in Sarawak.